Factors Affecting Postural Instability in Ménière's Disease. Issue 5 (26th August 2013) - Fujimoto, Chisato; Egami, Naoya; Kinoshita, Makoto; Sugasawa, Keiko; Yamasoba, Tatsuya; Iwasaki, Shinichi
Abstract : Objective: To assess the influence of factors that can affect the postural instability of Ménière's disease (MD) patients. Study Design: Case‐control study. Setting: Outpatient clinic in a university hospital. Subjects and Methods: Fifty‐four definite MD patients and 66 controls were included. Two‐legged stance tasks were performed in 4 conditions: eyes open with and without foam rubber and eyes closed with and without foam rubber. We examined 6 variables: the velocity of movement of the center of pressure (COP), the envelopment area traced by the movement of the COP, Romberg's ratio of velocity and area, and the foam ratios of velocity and area. For patients, stepwise multiple regression analyses were performed to explore the relationship between the 6 variables and the following independent variables: gender, age, the presence of abnormal caloric and/or cervical vestibular evoked myogenic potential (cVEMP) responses, the time elapsed since the last vertigo attack, and the disease duration. Results: The presence of MD had a significantly positive relationship with all 6 of the variables ( P <. 05). The presence of abnormal caloric and/or cVEMP responses had a significantly positive relationship with Romberg's ratio of velocity ( P <. 05) and area ( P <. 01). The shorter time interval from last vertigo attack to measurement had a significantly positive relationship with the foam ratio of area ( P <. 01). Conclusion: MD patients show poor postural performance, which is affected by the existence of their peripheral vestibular function and the shorter time interval from last vertigo attack to measurement.